Peranan Dokter Gigi dalam Meningkatkan Kualitas Hidup Pasien Mukositis dengan Leukemia Limfoblastik Akut (Laporan Kasus) - Theodora Adhisty Dwiarie; Nanan Nur’aeny; Nelly Nainggolan (Denta Journal Kedokteran Gigi, 2022)
Background: Mucositis, a painful condition common in patients undergoing chemotherapy, can decrease the patient's quality of life. Treatment of mucositis by dentists supports the improvement of general health conditions and the patient's quality of life. This case report aims to discuss a case of a patient with mucositis after undergoing chemotherapy treatment for acute lymphoblastic leukemia. Case: 21 years old female diagnosed with acute lymphoblastic leukemia, referred to the oral medicine department from internal medicine, complained of pain in oral mucosa and lockjaw in the last three days after chemotherapy treatment with methotrexate. Internal medicine prescribes ceftriaxone intravenous (IV), dexamethasone IV, chlorhexidine gargle, and nystatin. Intraoral examination showed erosive lesions in the tongue, labial, and buccal mucosa and was diagnosed as oral mucositis grade 3 according to the World Health Organization scale. Her quality-of-life score is 46 according to The Functional Assessment of Cancer Therapy-General (FACT-G) and 58 according to Oropharyngeal Mucositis Quality of Life (OMQoL). Case management: She was treated with magic mouthwash containing diphenhydramine HCL, sucralfate, and aluminum hydroxide-magnesium hydroxide. Chlorhexidine and nystatin were advised to stop. The patient was instructed to keep her oral hygiene by gargling with sodium chloride and povidone-iodine after eating. Five days after the therapy, her condition improved (grade 1), and there was an increase in the FACT-G and OMQoL scores to 54 and 93. Conclusion: Mucositis can cause pain in the patient. A dentist can help diagnose and provide appropriate treatment to reduce the patient's complaints and improve the patient's quality of life.